Sistem Informasi Kartu Pegawai Elektronik (SI-KPE) Berbasis Web dan Mobile KPE Berbasis Android Dengan Menggunakan Metode AES-128 - Yanuar Nurdiansyah; Slamin Slamin; Juniar Priaditama (INFORMAL: Informatics Journal, 2018)
East Java regional development Bank, known as the Bank of East Java was founded on august 17th 1951 in Surabaya. Bank of East Java has a lot of products and services for both civil society or non- civilservants.Oneofthemistheproduct elektronicservisservantcard(KPE).Datamanagementservices servants electronic card is very simple, make inefficient in terms of time and effort because the input file and file storage are still using manual system, as well as to disseminate announcements or events newest still using posters and other print media. File and information would be usefull if it is delivered to the user with an interest in the proper way. Currently, almost all file and information submitted throught the internet network. Security and confidentiality of file submitted via the internet is vulnerable to file theft by unauthorized parties. One way to maitain the security and confidentiality of such file is by using cryptographic methods. There are many cryptographic algorithms that are used to secure the file. One of which is an Algorithm Advanced Encryption Standard (AES). AES algorithm used in the reseacrh, namely AES-128 algorithm to encode digital files. So that the information contained in the file become more secure after converted into the file encrypt because the information can only be read by the party entitled. Employee card elektorinic information system (SI-KPE) and android based Mobile KPE using AES-128 method is a solution for Bank of East Java Jember branch